Seismic investigation of the γ Dor star KIC 6462033: The first results of Kepler and ground-based follow up observations. Issue Volume 9:Issue S301(2013) (18th February 2014) - Ulusoy, C.; Ulaş, B.; Damasso, M.; Carbognani, A.; Cenadelli, D.; Stateva, I.; Iliev, I. Kh.; Dimitrov, D.
Abstract: Preliminary results on the analysis of the Kepler light curve and photometric ground-based time series of γ Dor star KIC 6462033 (TYC 3144-646-1, V = 10.83, P = 0.69686 d) are presented in order to determine pulsation frequencies.